The Effect of Sunspace on Thermal Performance of Buildings in Hot and Dry Regions, Riyadh City as a Case Study - Mohammed Abanomi وليد (Journal of King Abdulaziz University: Environmental Design Sciences, 2021)
Due to the long summer season in Riyadh, most of the research activities in Saudi Arabia were dedicated to envi-ronmental design strategies for cooling. Little efforts have been done in research studies that are addressing the heating load design conservation in buildings. The Sunspace is one of the environmental design strategies that can be used to increase the indoor air temperature of the attached spaces during winter season. This research will evaluate the effectiveness of the Sunspace on the thermal performance of the indoor spaces in buildings located in Riyadh City. Two identical experimental rooms were built to achieve a comparison between base case room and the modified room that had an attached Sunspaces. Thermal assessment devices had been used to record the air temperature and relative humidity inside the two rooms and outside environment during winter time. The Sunspace was able to increase the indoor air temperature and early morning hours. The findings of this research illustrate the effectiveness of Sunspace to increase the indoor air temperature inside the buildings. The results of this research can be applied to all buildings in Riyadh City and in all buildings located in hot arid region.